Next-generation sequencing outperforms Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) in endometrial cancer molecular classification - Takuma Yoshimura; Kohei Nakamura; Tatsuyuki Chiyoda; Reika Takamatsu; Ryutaro Kawano; Eriko Aimono; Miho Kawaida; Kensuke Sakai; Yohei Masugi; Hiroshi Nishihara; Wataru Yamagami (BJC Reports)
Abstract Background We aimed to compare the values of next-generation sequencing (NGS) and Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) in redefining the molecular classification of endometrial cancer (EC). Methods We investigated the relationship between clinical outcomes and molecular subtypes of POLE, microsatellite instability-high (MSI-H), copy number low (CN-L), and copy number high (CN-H) classified by cancer gene panel testing for 145 cancer-related genes, as well as the immunohistochemical status of p53 and mismatch repair genes, in 200 cases of EC. Results The NGS-based classification identified CN-L subtype as the most prevalent (104/200, 52.0%), followed by MSI-H (38/200, 19.0%), POLE (33/200, 16.5%), and CN-H (25/200, 12.5%). Overall survival differed significantly for the four subtypes based on the NGS (p = 0.006) but not on the ProMisE (p = 0.117) classification. Additional mutations were identified for some POLE subtypes beyond the known hotspots, with 18.2% (6 of 33) showing concurrent MSI-H. Immunohistochemistry showed a p53 wild-type pattern for 12 (48%) CN-H cases, and there was no significant difference in prognosis depending on the p53 status in the CN-H subtype. Conclusions NGS surpassed ProMisE in EC molecular classification, offering precise stratification and prognostication. Our NGS platform has the potential to contribute to personalized treatment in EC.